Acid-base balance in acute ethylene glycol poisoning in rats treated with fomepizole - Przystanowicz, Jędrzej; Zielińska-Psuja, Barbara; Kowalówka-Zawieja, Joanna; Sommerfeld, Karina (Journal of Medical Science, 2014)
Introduction. Ethylene glycol (EG) is relatively nontoxic but undergoes a multi-step oxidation to toxic metabolites, aldehydes and acids. The accumulation of organic acids, mainly glycolates, leads to the development of profound, life-threatening metabolic acidosis. A key therapy is an antidotal treatment with fomepizole (4-MP), the inhibitor of the first step of EG biotransformation enzyme, alcohol dehydrogenase.Aim. The aim of the study was to demonstrate the efficacy of fomepizole in the prevention of acid-base balance disorders in acute ethylene glycol poisonings in rats.Material and methods. Adult male Wistar rats were given EG (p.o.) with single (i.p.) or multiple (p.o.) doses of 4-MP (EG 3830 and 5745 mg/kg, respectively, 4-MP in single dose of 10 mg/kg or 15 mg/kg followed by 10 mg/kg every 12 hours). Blood gas analysis was performed and blood pH, bicarbonate concentration and base excess were evaluated.Results and conclusions. The single dose of 4-MP was effective in preventing a decrease in blood pH, bicarbonate concentration and base excess during the entire experimental period (pH 7.35 vs 7.21 at hour 12, bicarbonate concentration 27.2 vs 18.3 mmol/dm3 at hour 8, base excess 1.8 vs -8.2 mmol/dm3 at hour 18). The multiple administration of 4-MP started 2 hours after EG poisoning resulted in rapid restoration of proper values of acid- -base balance parameters. Fomepizole is highly efficacious in restraining the acid-base balance disorders which are concomitant with acute ethylene glycol poisonings.